Detection of varicella zoster virus in genital specimens using a multiplex polymerase chain reaction. Issue 4 (5th August 2003) - Birch, C J; Druce, J D; Catton, M C; MacGregor, L; Read, T
Abstract : Objective: To compare the relative proportions of varicella zoster virus (VZV) and herpes simplex viruses in specimens obtained from the genital lesions of adults presenting with presumed genital herpes infection. Methods: Swabs of genital lesions from 6210 patients attending general practices, infectious diseases clinics within hospitals, or sexual health centres for treatment of their genital lesions were tested using polymerase chain reaction (PCR) technology. The multiplexed PCR was capable of detecting herpes simplex virus types 1 and 2 (HSV-1, HSV-2), VZV, and cytomegalovirus in a single sample. Results: A total of 2225 patients had viruses detected by PCR. HSV-1 was detected in 36%, HSV-2 in 61%, and VZV in 2.9% of PCR positive samples. Of the 65 patients with VZV genital infection, many were thought to have HSV infection before laboratory testing. Conclusions: The finding of VZV in nearly 3% of virus positive genital specimens demonstrates that this virus needs to be considered as a differential diagnosis for genital herpetic lesions. Advice provided to patients with VZV genital infection regarding the source of infection, likelihood of recurrence, and potential for transmission of the virus will be different from that given to patients with HSV infection.